Kill or cure an illustrated history of medicine - Parker, Steve 1952- (Dorling Kindersley Limited, 2013)
"Drawing on his wealth of knowledge about the human body and medical science, Steve Parker blends historical accounts and lucid explanations to illuminate the intriguing development of humankind's most remarkable achievements. Kill or Cure not only tells the story of medicine, it also illustrates the science, the equipment, and the great medical practitioners. Witness early, bloody, anesthetic-free operations; see the first crude surgical instruments; trace the mapping of the circulatory system; and follow the painstaking detective work that led to the decoding of the human genome."-- Dust jacket flap